Consumption of a High-Fat Diet Alters Perineuronal Nets in the Prefrontal Cortex - P. M. Dingess; J. H. Harkness; M. Slaker; Z. Zhang; S. S. Wulff; B. A. Sorg; T. E. Brown (Neural Plasticity)
A key factor in the development of obesity is the overconsumption of fatty foods, which, in addition to facilitating weight gain, alters neuronal structures within brain reward circuitry. Our previous work demonstrates that sustained consumption of a high-fat diet (HFD) attenuates spine density in the prefrontal cortex (PFC). Whether HFD promotes structural adaptation among inhibitory cells of the PFC is presently unknown. One structure of interest is the perineuronal net (PNN), a specialized extracellular matrix surrounding, primarily, parvalbumin-containing GABAergic interneurons. PNNs contribute to synaptic stabilization, protect against oxidative stress, regulate the ionic microenvironment within cells, and modulate regional excitatory output. To examine diet-induced changes in PNNs, we maintained rats on one of three dietary conditions for 21 days: ad libitum chow, ad libitum 60% high fat (HF-AL), or limited-access calorically matched high fat (HF-CM), which produced no significant change in weight gain or adiposity with respect to chow controls. The PNN “number” and intensity were then quantified in the prelimbic (PL-PFC), infralimbic (IL-PFC), and ventral orbitofrontal cortex (OFC) using Wisteria floribunda agglutinin (WFA). Our results demonstrated that fat exposure, independent of weight gain, induced a robust decrease in the PNN intensity in the PL-PFC and OFC and a decrease in the PNN number in the OFC.